Social Portrait of a Foreign Language Teacher at the Turn of XIX-XX Centuries - M. N. Vetchinova (Научный диалог)
A social portrait of a gymnasium teacher of ancient and new languages at the turn of the XIX-XX centuries is presented. The mission of the teacher, his study load, the ability to combine the teaching of several subjects of the gymnasium course are shown. Information about the features of work in the position of classes mentors is presented. The forms of work that were paid extra, as well as those for which teachers did not receive any payment, were highlighted. Information is provided on the number of lessons per week and the amount paid. The financial situation of the teacher, in particular, the cost of rent, nutrition, spiritual development, is characterized. The requirements of teachers on increasing salaries and reducing the workload are given. The appeal of the “Society for the mutual assistance of pedagogical rank” Board to teachers of the country with a request to intensify the work in educational institutions to raise funds to help teachers in need is analyzed. It is concluded that the volume of the academic load and material reward did not correspond to the high sociocultural mission that was assigned to the teachers, but during this historical period, the teacher was the standard of education, culture, unquestioned authority, for which he earned respect from students, their parents and public.